Resonance Raman scattering by intersubband plasmon-phonon excitations in InAs/AlSb structures - Valakh, M.Ya.; Strelchuk, V.V.; Kolomys, O.F.; Hartnagel, H.L.; Sigmund, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Intersubband plasmon-phonon excitations in InAs/AlSb with InSb- and AlAs-like interfaces were studied using the Raman scattering method. It was found that InSb interface is characterized by a decreasing concentration and increasing mobility of 2D electrons in InAs quantum wells. In the case of AlAs interface at the heterojunction quantum well - barrier, the formation of AlSb₁₋xAsx solid solution takes place. Revealed are considerable concentration changes for 2D electrons at low temperatures in dependency on the excitation quantum energy.